FREQUENCY OF PEDIATRIC BRAIN TUMORS IN TERTIARY CARE INSTITUTE OF PAKISTAN AND COMPARISON WITH INTERNATIONAL DATA - Qurni, Muhammad Owais; Tariq, Hassan; Tahir, Hiba; Din, Hafeez Ud; Mansur, Hamza; Aslam, Maria (Pakistan Armed Forces Medical Journal, 2021)
Objective: To analyze the histological spectrum of pediatric brain tumors (PBT) in Pakistani population and to compare the results with international data.Study Design: Retrospective observational study.Place and Duration of Study: Armed Forces Institute of Pathology, Rawalpindi, from Jan 2015 and Dec 2019.Methodology: This data was analyzed using the latest World Health Organization (WHO) classification of Tumors of Central Nervous System 2016. The cases were divided in 5 categories according to age (0-2, 3-5, 6-8, 9-11 & 12-14 years).Results: A total of 43 cases were included in the study. Of these cases, 26 (60.46%) were male and 17 (39.5%) were female. Male to female ratio was 1.5-1. The 6-8 year age group had the highest number of tumors while 0-2 year age group had the least. Mean age of diagnosis was 7.6 years. Ependymoma wasthe most common morphological type with 12 cases (28%) followed by pilocytic astrocytoma, diffuse glioma with 10 cases each (23%) and medulloblastoma with 9 cases (21%). Least common tumor subtype was Ewing sarcoma. Ependymoma were mostly of grade 3 (64%), pilocytic astrocytoma and medulloblastoma were of grade 1 and grade 4 respectively by definition, and diffuse gliomas were mainly of grade 2 (57%) type.Conclusion: Ependymoma and pilocytic astrocytomaare the most frequent types of pediatric brain tumors in our region which follows the same trend as mentioned in western and regional literature.